sum the following series to n terms 2+5+10+17+26+.................................

Asked by coolameet08 | 14th Feb, 2010, 12:41: PM

Expert Answer:

2 + 5 + 10 + 17 + 26 + ....  = (12+1) + (22 + 1) + (32+1) + (42+1) + (52+1) + ...

= 12+ 22 + 32 + 42 + 52 + .......(1 + 1 +1 + +1 + +  n times)

= [(n(n+1)(2n+1))/6] +  [n(n+1)/2]

= n(n+1)(n+2)/3

Regards,

Team,

TopperLearning.

Answered by  | 14th Feb, 2010, 02:12: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.